Language Style in the Lyrics of the Song Salam Alaikum - Haris J - Nabila, Annisa Nabila; Selviana, Ika (Dinamika Bahasa dan Budaya, 2024)
The language style explores the linguistic styles employed in the song "Salam 'Alaikum." Through a lyrical analysis, it examines the use of linguistic devices such as metaphor, simile, repetition, and cultural references. The song utilizes language to convey messages of peace, unity, and cultural pride, employing a blend of traditional and contemporary linguistic elements. Additionally, it investigates how linguistic choices contribute to the song's overall theme and emotional resonance, highlighting the importance of language in shaping cultural narratives and fostering connection within diverse communities. Through a close reading and thematic analysis, this paper explores how the use of Arabic greetings, religious references, and inclusive language constructs a message of unity, peace, and cultural appreciation. Furthermore, it investigates the song's impact on its audience, particularly within the context of contemporary global discourse on multiculturalism and religious tolerance. Overall, this analysis illuminates the role of language in shaping cultural narratives and fostering interfaith dialogue through the medium of music. Keywords: language style, stylistics, song lyrics